2007
DOI: 10.1097/01.sla.0000231758.07868.71
|View full text |Cite
|
Sign up to set email alerts
|

Partial Hepatectomy With Wide Versus Narrow Resection Margin for Solitary Hepatocellular Carcinoma

Abstract: For macroscopically solitary HCC, a resection margin aiming grossly at 2 cm efficaciously and safely decreased postoperative recurrence rate and improved survival outcomes when compared with a gross resection margin aiming at 1 cm, especially for HCC < or =2 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
317
2
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 440 publications
(336 citation statements)
references
References 31 publications
9
317
2
8
Order By: Relevance
“…In comparison to other studies evaluating the recurrence in HBV related HCCs; the role of the resection margin is also controversial. Some studies supported a wide safety margin (more than 1 cm) and found it a significant predictor of tumour recurrence [13,14]. Other studies found no significant association between safety margin and tumour recurrence [15][16][17].…”
Section: Discussionmentioning
confidence: 82%
“…In comparison to other studies evaluating the recurrence in HBV related HCCs; the role of the resection margin is also controversial. Some studies supported a wide safety margin (more than 1 cm) and found it a significant predictor of tumour recurrence [13,14]. Other studies found no significant association between safety margin and tumour recurrence [15][16][17].…”
Section: Discussionmentioning
confidence: 82%
“…Among patients who presented recurrence, 4 had liver cirrhosis (HCV-related in 2 cases, steatohepatitic in one case and alcohol-related in the remaining one), 2 were affected by nonalcoholic steatohepatitis, and 1 had healthy liver. In the eight patients who did not display recurrence, the median follow-up was 21 months (range [16][17][18][19][20][21][22][23][24][25][26]. The only significant difference found between subjects with and without recurrence was age displayed recurrence, compared to those who remained cancer-free during follow-up (p=0.02) ( Table 4 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Portal hypertension, hepatic venous pressure gradient (HVPG) ≥ 10 mmHg, was found to be the best predictor of postoperative liver decompensation and poor long-term outcomes in compensated cirrhotic patients undergoing hepatic resection [10]. Postresection tumor recurrences often have multifocal presentations and repeat resections are rarely ideal, instead, salvage liver transplantation, or other loco-regional therapies, with or without oral multi-kinase inhibitors are more suitable.…”
Section: Resectionmentioning
confidence: 99%